Sustainable Manufacturing Practices in a Textile Company: A Case Study - Rushanim Hashim; Norsiah Hami; Salmah Omar; Shafini Mohd Shafie; Poh Wei Lin; Muhardi Muhardi; Cici Cintyawati; Rabiatul Adwiyah; Nur Yuhainis Ab Wahab (International Journal of Supply Chain Management, 2020)
The main purpose of the present study is to develop an in-depth understanding of sustainable manufacturing practices implemented by a textile company. A single case study has been employed in which a company located in Penang was chosen as a case to be studied. A face to face interview was conducted to get in-depth information from the respondent to fulfil the research objectives. The study found that the company being studied has implemented several sustainable manufacturing practices such as recycling materials, reducing hazardous input materials, emphasizing employees’ well-being, managing waste in a sustainable way, and adopting solar energy in its operation. Furthermore, the findings of this study provide a great foundation for a better understanding of sustainable manufacturing practices and their contribution to sustainability performance, particularly in the context of the textile industry. The findings of this study also have a noticeable implication, especially for the textile company and other practitioners, to evaluate their current manufacturing practices and explore the strategy that could assist them to step forward to reduce the impact of their operation on the natural environment.